Biodegradable MnFe-hydroxide nanocapsules to enable multi-therapeutics delivery and hypoxia-modulated tumor treatment. Issue 17 (31st March 2020) - Liao, Linhua; Cen, Dong; Fu, Yike; Liu, Bin; Fang, Chao; Wang, Yifan; Cai, Xiujun; Li, Xiang; Wu, Hao Bin; Han, Gaorong
Abstract : Fine nanocapsules based on MnFe hydroxides, showing high loading capacity, O2 induction and biodegradation, were synthesized for effective synergistic therapies. Abstract : Developing drug delivery platforms that can modulate a tumor microenvironment and deliver multiple therapeutics to targeted tumors is critical for efficient cancer treatment. Achieving these platforms still remains a great challenge. Herein, biodegradable nanocapsules based on MnFe hydroxides (H-MnFe(OH) x ) have been developed as a new type of cargo delivery with high loading capacity and catalytic activity, enabling synergetic therapy with promoted efficacy by relieving hypoxia in tumor tissues. As a proof of concept, a photosensitizer (indocyanine green, ICG) and a chemotherapeutic drug (doxorubicin, DOX) are co-loaded in nanocapsules and selectively released upon degradation of the nanocapsules in the acidic tumor microenvironment, and are promoted by near infrared irradiation. Meanwhile, Mn 2+ /Fe 3+ ions released from the degradation of nanocapsules catalyze the conversion of H2 O2 in a tumor microenvironment into oxygen, which modulates tumor hypoxia and dramatically boosts multimodal therapies. Remarkable synergistic anticancer outcomes have been demonstrated both in vitro and in vivo, paving the way towards future multifunctional therapeutic platforms.